THE EFFECT OF CARBON MONOXIDE’S DONOR CORM-2 ON ERYTHROCYTE AQUAPORINS - Beschasnyi, S.P.; Hasiuk, O.M. (World of Medicine and Biology, 2021)
Carbon monoxide is part of group of gas transmitters, which are produced by almost all cells and involved in many mechanisms of internal and external communication between cells. Carbon monoxide-releasing molecules are promising for therapeutic use. Such donors include tricarbonyldichlororuthenium (II) dimer. For the research, the aquaporins 1 and 3 were blocked in erythrocyte membranes with the use of mercury chloride and silver nitrate, and then they were added to hypo–, iso– and hyperosmolar solutions. However, tricarbonyldichlororuthenium (II) dimer does not bind to aquaporins 1, but this effect is due to the effect on aquaporins 3. This effect is dose-dependent: the most active concentration was 6–50 μM. It is arguable that tricarbonyldichlororuthenium (II) dimer increases the resistance of erythrocytes to hypertensive stress, stabilizes their volume in a hyper- and hypo-tonic environment by activating aquaporins 3.
Keywords: AQP1; AQP3; gas transmitter; erythrocyte membrane